Cellular Fibroma of Tendon Sheath With Novel TNC-USP6 Gene Fusion Clinically Mimicking Arthritis in a 7-Year-Old Boy. (March 2022) - Eisenberg, Joshua M; Buckwalter V, Joseph A; Snow, Anthony N; Davick, Jonathan
Cellular fibroma of tendon sheath (CFTS) is a rare, benign myofibroblastic neoplasm of tenosynovial soft tissues closely resembling nodular fasciitis (NF), but is histomorphologically distinct from classic fibroma of tendon sheath (FTS). We report a case of a pediatric patient with thumb swelling clinically concerning for arthritis with a biopsy demonstrating myofibroblastic proliferation with features consistent with NF/CFTS, and molecular studies confirming the presence of a USP6 gene fusion (TNC-USP6). This case highlights a unique clinical presentation of CFTS in a pediatric patient mimicking an inflammatory or reactive/non-neoplastic musculoskeletal disorder and the increasingly crucial role of molecular testing to differentiate a reactive myofibroblastic process from a neoplasm. Moreover, this report identifies TNC as a new fusion partner to USP6 fusion partner adding to our growing understanding of the USP6-rearranged family of tumors.